The co-application of arbuscular mycorrhizal fungus and Trichoderma on anthracnose disease in common vetch - He, Jia; Li, Faxi; Zheng, Rongchun; Bai, Meiting; Wang, Ping; Duan, Tingyu (Frontiers in Microbiomes, 2025)
IntroductionCommon vetch (Vicia sativa) is an important legume used for forage and green manure. Anthracnose caused by Colletotrichum spinaciae is a significant disease affecting common vetch, resulting in significant damage and yield reductions. Furthermore, there is a lack of effective control methods for this disease.MethodsThis study evaluated the control of anthracnose in V. sativa under greenhouse conditions, focusing on the efficacy of 25% pyraclostrobin, the arbuscular mycorrhizal (AM) fungus Glomus tortuosum, and Trichoderma longibrachiatum, both individually and in combination.ResultsThe results showed that 25% pyraclostrobin, G. tortuosum, and T. longibrachiatum both individually and in combination reduced the incidence of anthracnose by 53.85%, 34.62%, 34.62%, and 15.39%, respectively. Correspondingly, the disease index decreased by 68.97%, 34.48%, 32.76%, and 20.69%. Notably, the application of G. tortuosum and T. longibrachiatum alone enhanced common vetch defense enzyme activities of peroxidase, catalase, superoxide dismutase, and polyphenol oxidase by 23.57% and 22.10%, 27.12% and 26.76%, 21.54% and 19.33%, and 35.79% and 34.35%, respectively (P < 0.05). Moreover, the application of AM fungi and Trichoderma led to increased activities of soil urease, catalase, and neutral phosphatase by 12.77% to 111.17%, as well as improved nitrogen and phosphorus uptake by 12.12% to 13.88% and 13.91% to 35.79%, respectively.DiscussiomOur findings highlight that G. tortuosum and T. longibrachiatum can effectively induce resistance against anthracnose in common vetch, demonstrating significant control efficacy.